National Achievement Survey of Class III - Achievement Highlights - Chandrasekhar, K. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
National Achievement Surveys (NAS) are the national assessment of what students know and can do in various subjects at elementary and secondary education in India. The National Policy on Education, 1986 emphasises periodical Achievement Surveys at different stages of school education as a means to assess the health of the education system. To know the impact of the various inputs provided to the system through different regional and national schemes, a study of class III students‟ achievement level in Mathematics and Language has been conducted. The researcher is presenting achievement of students in Mathematics and Language and the variations in gender wise and location wise performance based on the data collected through achievement tests administered to 1,04,374 students, questionnaires to 7,046 schools covering 298 districts of 34 States and Union Territories of India.